2003
DOI: 10.1021/es034480g
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the World Trade Center and PCBs, PBDEs, PCDD/Fs, PBDD/Fs, and Chlorinated Biphenylenes in Water, Sediment, and Sewage Sludge

Abstract: Ash-laden runoff samples collected near Ground Zero soon after the September 11, 2001 attack on the World Trade Center (WTC) and subsequent fire demonstrate the release of polychlorinated biphenyls (PCBs), polybrominated dipheyl ethers (PBDEs), polybrominated dibenzo-p-dioxins and polybrominated dibenzofurans (PBDD/Fs), polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), and tetra- and pentachlorinated biphenylenes (PCBPs) from the incident. Relative abundances of PCDD/F congeners in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…Briefly, dioxin and DLCs bind to AhR followed by nuclear translocation and binding to dioxinresponsive element (DRE) in target gene promoters (Denison and Nagy 2003). In addition to the chlorinated compounds, the environmental levels of polybrominated dibenzo-p-dioxins/furans (PBDD/Fs) have been increasing along with the ubiquitous use of brominated organic chemicals (Litten et al 2003;Hayakawa et al 2004;Wang et al 2010). Brominated DLCs exert their effects primarily via the AhR signaling pathway and are found to be approximately equally potent as their chlorinated analogues (Behnisch et al 2003;Olsman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, dioxin and DLCs bind to AhR followed by nuclear translocation and binding to dioxinresponsive element (DRE) in target gene promoters (Denison and Nagy 2003). In addition to the chlorinated compounds, the environmental levels of polybrominated dibenzo-p-dioxins/furans (PBDD/Fs) have been increasing along with the ubiquitous use of brominated organic chemicals (Litten et al 2003;Hayakawa et al 2004;Wang et al 2010). Brominated DLCs exert their effects primarily via the AhR signaling pathway and are found to be approximately equally potent as their chlorinated analogues (Behnisch et al 2003;Olsman et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that both PCBs and PBDEs possess dioxin-like activity, and all of them are toxic, endocrine disrupting, and probably carcinogenic [3,4]. Because all these three groups of pollutants are ubiquitous, it is likely that they co-exist in most environmental matrices [5][6][7][8][9]. Therefore, simultaneously monitoring of their levels in environmental samples is highly desired in order to protect human health.…”
Section: Introductionmentioning
confidence: 99%
“…Because ECD is non-selective, not only the interferences from sample matrix are difficult to avoid, but also the interfering among the target compounds can be substantial, especially when their concentration levels differ dramatically. A few studies were published regarding to the simultaneous analysis of these three toxic chemical families in a single sample [7][8][9]. But none of them had completely separated PBDEs from PCBs although it is known that they may interfere with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the rescue workers developed persistent coughs, headaches, memory disturbance and other symptoms while working on the site 2 . USEPA measurements of benzene, dioxins and polychlorinated biphenyls (PCBs) were elevated in the air in the weeks after the collapse 3 . Dioxins slowly returned to normal background levels after three months 3 .…”
Section: Introductionmentioning
confidence: 99%
“…USEPA measurements of benzene, dioxins and polychlorinated biphenyls (PCBs) were elevated in the air in the weeks after the collapse 3 . Dioxins slowly returned to normal background levels after three months 3 . The New York (NY) Department of Environmental Conservation (DEC) analyzed dust/ash samples collected close to the WTC site after September 11, 2001.…”
Section: Introductionmentioning
confidence: 99%